2019
DOI: 10.3389/fninf.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying How Staining Methods Bias Measurements of Neuron Morphologies

Abstract: The process through which neurons are labeled is a key methodological choice in measuring neuron morphology. However, little is known about how this choice may bias measurements. To quantify this bias we compare the extracted morphology of neurons collected from the same rodent species, experimental condition, gender distribution, age distribution, brain region and putative cell type, but obtained with 19 distinct staining methods. We found strong biases on measured features of morphology. These were largest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Among the density maps, the Z density maps did not perform differently from XZ density maps ( δ = 0.006 ± 0.02, z = 0.37, p = 0.71), while YZ density maps performed much worse in the three V1 data sets ( δ = 0.14 ± 0.05, z = 2.84, p = 0.005, average across V1 pairs only) but very similar in the bipolar data set ( δ = 0.01 ± 0.02, z = 0.77, p = 0.44). Indeed, the y direction is mostly meaningless in the V1 data as the slices are flattened during the biocytin staining process (Farhoodi et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the density maps, the Z density maps did not perform differently from XZ density maps ( δ = 0.006 ± 0.02, z = 0.37, p = 0.71), while YZ density maps performed much worse in the three V1 data sets ( δ = 0.14 ± 0.05, z = 2.84, p = 0.005, average across V1 pairs only) but very similar in the bipolar data set ( δ = 0.01 ± 0.02, z = 0.77, p = 0.44). Indeed, the y direction is mostly meaningless in the V1 data as the slices are flattened during the biocytin staining process (Farhoodi et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, tissue shrinkage and staining method can affect the measured morphology (Farhoodi et al 2019 ). In our study all three data sets obtained through biocytin staining (V1 L2/3, V1 L4, V1 L5) showed flattening of the cortical slice ( y -direction) which made XY density maps perform worse in comparison to other projections.…”
Section: Discussionmentioning
confidence: 99%
“…We used neuromorphr to obtain information about 40599 mammalian neurons from NeuroMorpho.org, in the brain region 'neocortex', from 193 different laboratories. However, it is quite difficult to compare morphologies acquired from different laboratories, that have used different imaging pipelines, neuron reconstruction tools and staining protocols (Farhoodi et al, 2019). We can use neuromorphr to access neuron metadata on NeuroMorpho.org, and choose only those neurons from the same laboratory (Bob Jacobs'), that have been obtained using a Golgi stain and the reconstruction software NeuroLucida, and that are classed as a principal cell (Anderson et al, 2010(Anderson et al, , 2009Jacobs et al, 2018Jacobs et al, , 2016Jacobs et al, , 2015Jacobs et al, , 2011Jacobs et al, , 2001Jacobs et al, , 1997Reyes et al, 2016;Travis et al, 2005), giving us 3174 neurons.…”
Section: Figure Legendsmentioning
confidence: 99%
“…The representations investigated here are purely descriptive and do not provide deeper mechanistic insight, compared e.g. to generative models of the growth process of neurons during development (van Pelt and Schierwagen, 2004;Cuntz et al, 2010;Memelli et al, 2013;Wolf et al, 2013;Fard et al, 2018;Farhoodi et al, 2019). Ideally, a mechanistically grounded feature representation would perform at least on par with density maps for cell type discrimination while yielding parameters that are more easily interpretable.…”
Section: Discussionmentioning
confidence: 99%
“…Among the density maps, the Z density map did not show a significant difference from XZ (δ = 0.006 ± 0.02, z = 0.37, p = 0.71), while YZ was much worse than XZ in the three V1 data sets (δ = 0.14±0.05, z = 2.84, p = 0.005, average across V1 pairs only) but very similar in the bipolar data set (δ = 0.01±0.02, z = 0.77, p = 0.44). Indeed, the y direction is mostly meaningless in the V1 data as the slices are flattened during the biocytin staining process (Farhoodi et al, 2019).…”
Section: Predictive Performance Of Feature Representationsmentioning
confidence: 99%